Analysis of Islamic Education Values in the Massuro Baca Tradition in the Tamarampu Environment, Bontoa Village, Mandai District, Maros Regency - Rizal, Rizal; Tang, Muhammad; Palili, Sampara; Ismail, Ismail; Susono, Juhasdi (International Journal on Advanced Science, Education, and Religion, 2025)
The Massuro Baca tradition is one of the cultural practices of the Makassar Bugis community which is still preserved to this day and has a close relationship with Islamic values. This study aims to analyze the values of Islamic education contained in the Massuro Baca tradition in the Tamarambu Environment, Bontoa Village, Mandai District, Maros Regency. This research uses a descriptive qualitative approach with field research methods. Data collection was carried out through observation, in-depth interviews, and document analysis. Data analysis was carried out through the stages of data reduction, data presentation, and conclusion drawn, and its validity was tested through triangulation techniques. The results of the study show that the Massuro Baca tradition contains Islamic educational values which include the values of faith, worship, and morals. These values are reflected in the practice of prayer, tawassul, almsgiving, gratitude, sima'an Al-Qur'an, friendship, and helping. These findings confirm that the Massuro Baca tradition functions as a non-formal Islamic educational medium that plays a role in shaping religious character, strengthening social solidarity, and maintaining harmony between Islamic teachings and local wisdom of the community.